Immune environment of high-TIL breast cancer: triple negative and hormone receptor positive HER2 negative - Su-Jin Shin; Inho Park; Heounjeong Go; Jiwon Ko; Yangkyu Lee; Jee Hung Kim; Sung Gwe Ahn; Joon Jeong; Soong June Bae; Yoon Jin Cha (npj Breast Cancer)
Abstract This study explores differences in immune cell (IC) composition and spatial distribution between triple-negative breast cancer (TNBC) and hormone receptor-positive, HER2-negative breast cancer (HR + HER2-BC) in high-TIL (≥60%) cases, focusing on PD-L1 status. Using multiplex immunofluorescence on resected tumor tissues from 18 TNBC and 14 HR + HER2-BC cases, we analyzed IC types (CD20, CD8, CD4, FOXP3) and their spatial interactions. TNBC showed a unique IC composition characterized by a higher proportion of CD8 + IC (stroma: 27% vs 17%, p < 0.001; tumor: 54% vs 31%, p < 0.001) and CD4 + FOXP3 + IC (stroma: 3.9% vs 3.0%, p = 0.036), compared to HR + HER2-BC. Notably, PD-L1 positive TNBC cases demonstrated denser infiltration CD4 + FOXP3 + IC in the stromal region compared to HR + HER2-BC (146.4 ± 67.1/mm2 vs 114.3 ± 146.9/mm2, p = 0.036), along with pronounced IC clustering near TC. Both tumor subtypes displayed varied IC compositions based on PD-L1 status. In conclusion, IC composition and spatial distribution in high-TIL TNBC and HR + HER2-BC significantly differ, influenced by PD-L1 status.